Evaluation of Sanitation Standard Operating Procedure (SSOP) Sambal Bawang in MSMEs XY: Evaluasi Sanitation Standard Operating Procedure (SSOP) Sambal Bawang di UMKM XY - Mufida Naima Rohmah; Riski Ayu Anggreini (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Sambal is a product that is very popular with Indonesian people. UMKM Products produced by UMKM XY have received various certifications for food safety. One of the things that must be considered in maintaining food safety is the implementation of the SSOP (Sanitation Standard Operating Procedure) aspect. The SSOP application is very important to implement in order to ensure sanitation and cleanliness that will affect the product. The purpose of this activity is to review and evaluate the implementation of SSOP in UMKM XY. This activity will later be able to maximize the implementation of SSOP in UMKM XY. The form of activity is carried out through observation, interviews, literature study, and evaluation. The result of this activity is that UMKM XY employees are able to understand the SSOP application that has been explained. This is evidenced by a change in employee habits who pay more attention to the application of SSOP in production process activities, such as using mineral water that has been tested for the material rinsing process, employees wearing complete uniforms and attributes, as well as regular cleaning and monitoring throughout the production site.